The Impact of the Protection of Personal Information Act No 69 of 2013 on Direct Marketing and Insurance consumer protection in South Africa - Barnard, Jacolien (University of Pretoria, 2021)
Mini Dissertation (LLM)--University of Pretoria 2020.